(untitled) (The Research of Medical Science Review, 2024)
INTRODUCTION: Newborns with the gestational age of less than 32 weeks are by default immune compromised, and possess only approximately one half of the cord blood Ig G seen in term infants. Furthermore, extremely preterm infants are immunologically immature manifested by decreased immune components, reduced poly morphonuclear chemotaxis and decreased ability to fight infections. AIM AND OBJECTIVES: That is why, the purpose of this study was to evaluate the effectiveness of such approach as repeated consecutive monitoring of the C-reactive protein level together with the antibiotics administration to improve the sepsis outcomes in premature infants.MATERIALS AND METHODS: Sixty preterm infants clinically diagnosed with sepsis were taken randomly in the study group and control group during one year (May 2019 to April 2020) in Fauji Foundation Hospital Neonatal Intensive Care Unit. In addition to the treatment, the study group’s ENT was monitored with CRP levels.RESULTS: The mean neonatal age distribution was 5.72 days ±3.86/ SI Units. Of the 60 neonates a, 32 (53.3%) were male while 28 (46.7%) were female. Sepsis was proved in 42/60; 70% through blood culture while sepsis was negatives through blood culture in 18/60; 30%. After 72 hours, 41 (68%) neonates had a positive CRP result, while 19 (32%) were negative. The sensitivity of CRP at 72 hours in diagnosing acute neonatal sepsis was 73.17%. The specificity was 42.10%. The positive predictive value (PPV) of CRP was 73.17%, and the negative predictive value (NPV) was 42.10%, and overall, the diagnostic accuracy of CRP in diagnosing neonatal sepsis at 72 hours was 63.33%.CONCLUSION: This study demonstrates that CRP is a valuable tool for diagnosing neonatal sepsis in preterm babies, with decent sensitivity (73.17%) and a positive predictive value of 73.17%, making it effective in identifying true sepsis cases. However, its lower specificity (42.10%) and negative predictive value (42.10%) indicate limitations in ruling out non-sepsis cases. With a diagnostic accuracy of 63.33%, CRP can be used alongside clinical assessment and blood cultures to guide effective management of neonatal sepsis.